Integrated approach with UHPLC-Q-Exactive-tandem mass spectrometry, network analysis, and molecular docking to determine potential active compounds and mechanisms of Rhizoma Musae decoction in osteoarthritis treatment - Zhang, Jian; Shen, Wanyan; Liu, Fanzhi; He, Hehe; Han, Shuquan; Luo, Lina (Frontiers in Pharmacology, 2025)
Objective: This study aimed to identify the potential active compounds in Rhizoma Musae decoction and understand their mechanisms of action in osteoarthritis treatment.Methods: UHPLC-Q-Exactive-MS/MS technology was used for an in-depth analysis of the chemical compounds present in Rhizoma Musae decoction. A network analysis approach was used to construct a comprehensive network of compounds, targets, and pathways, which provided insights into the molecular mechanisms of Rhizoma Musae decoction in osteoarthritis treatment.Results: The integrated analysis revealed the presence of 534 chemical compounds in Rhizoma Musae decoction, with 7beta-hydroxyrutaecarpine, 7,8-dihydroxycoumarin, pinocembrin diacetate, and scopoletin being identified as potential active compounds. Potential targets such as GAPDH, AKT1, TNF, IL6, and SRC were implicated in key pathways including MAPK signaling pathway, lipid and atherosclerosis, PI3K-Akt signaling pathway, and IL-17 signaling pathway. Molecular docking studies showed significant binding affinity between the core targets and key components. In vitro cell experiments have demonstrated that RM decoction can enhance cell proliferation and upregulates the expression of TNFα, IL-6, and SRC, while down-regulating the expression of GAPDH and AKT1. Conclusion: The potential active compounds present in Rhizoma Musae decoction influence specific targets and signaling pathways involved in osteoarthritis pathogenesis, providing new insights for the functional development and utilization of RM.